Denitrifying capabilities of Tetrasphaera and their contribution towards nitrous oxide production in enhanced biological phosphorus removal processes. (15th June 2018) - Marques, Ricardo; Ribera-Guardia, Anna; Santos, Jorge; Carvalho, Gilda; Reis, Maria A.M.; Pijuan, Maite; Oehmen, Adrian
Abstract: Denitrifying enhanced biological phosphorus removal (EBPR) systems can be an efficient means of removing phosphate (P) and nitrate (NO3 − ) with low carbon source and oxygen requirements. Tetrasphaera is one of the most abundant polyphosphate accumulating organisms present in EBPR systems, but their capacity to achieve denitrifying EBPR has not previously been determined. An enriched Tetrasphaera culture, comprising over 80% of the bacterial biovolume was obtained in this work. Despite the denitrification capacity of Tetrasphaera, this culture achieved only low levels of anoxic P-uptake. Batch tests with different combinations of NO3 −, nitrite (NO2 − ) and nitrous oxide (N2 O) revealed lower N2 O accumulation by Tetrasphaera as compared to Accumulibacter and Competibacter when multiple electron acceptors were added. Electron competition was observed during the addition of multiple nitrogen electron acceptors species, where P uptake appeared to be slightly favoured over glycogen production in these situations. This study increases our understanding of the role of Tetrasphaera -related organisms in denitrifying EBPR systems. Highlights: Tetrasphaera less able to remove P anoxically as compared to Accumulibacter . Tetrasphaera performed the majority of the N removal (>80%), in this mixed culture. Tetrasphaera could lead to N2 O emissions under certain conditions. Electron competition was observed with multiple nitrogen electron acceptors. This study increases our knowledge of denitrifying EBPR systems and N2 O emissions.